2019
DOI: 10.1053/j.gastro.2018.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis in Children

Abstract: Acute, acute recurrent, and chronic forms of pancreatitis have been increasingly diagnosed in children in the past 2 decades. Risk factors in the pediatric group are broad and appear to be strikingly different compared with the adult cohort. However, the disease burden and impact on quality of life are surprisingly similar in children and adults. This review summarizes the definitions, epidemiology, risk factors, diagnosis, and management of pediatric pancreatitis, identifies features that are unique to the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 109 publications
(122 reference statements)
7
109
0
4
Order By: Relevance
“…Genetic and structural defects represented a significant percentage of patients with recurrent and chronic pancreatitis. This high frequency is similar to that seen in other studies of pediatric pancreatitis [19, 27, 33, 35]. This highlights the importance of pursuing an investigation for an underlying genetic or structural etiology, especially in those presenting with a recurrent episode of pancreatitis or evidence of chronic pancreatitis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Genetic and structural defects represented a significant percentage of patients with recurrent and chronic pancreatitis. This high frequency is similar to that seen in other studies of pediatric pancreatitis [19, 27, 33, 35]. This highlights the importance of pursuing an investigation for an underlying genetic or structural etiology, especially in those presenting with a recurrent episode of pancreatitis or evidence of chronic pancreatitis.…”
Section: Discussionsupporting
confidence: 85%
“…Other categories were determined in a post hoc manner. We assumed that alcohol would not be a significant etiology in this age group due to previous research showing that alcohol use disorder is nonexistent to extremely rare in the preadolescent age range, use of alcohol among children has declined significantly over the last 10 years, and that alcohol has been found to be nearly negligible as an etiology for pediatric pancreatitis [1925]. Patients with traumatic pancreatitis were identified and excluded as this group has been studied extensively.…”
Section: Methodsmentioning
confidence: 99%
“…For AP with speci c causes, such as bile duct stones, anatomical abnormalities, bile duct dilatation, etc., it has been suggested that surgery should be performed as soon as possible after the condition is controlled and stable, to prevent recurrence [11,21]. In the literature [22], the mortality rate of pediatric AP is less than 5%, which is signi cantly lower than that of adult AP, possibly because: (1) Alcoholic pancreatitis is rare in pediatric cases, and alcoholic pancreatitis is a known cause of high mortality, with a mortality rate as high as 30.6% [23]. (2) With age, adults may lose some critical protective mechanism, which children retain [6].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the actuarial incidence of chronic pancreatitis in children is increasing and (2 cases:100,000 people/year, with overall prevalence of 6 cases:100,000 inhabitants). The most common genetic alterations are SPINK1, PRSS1, CEL-HYB, CFTR, CAP1, CTRC, CEL (18, 19). After the exclusion of more obvious and prevalent toxic causes such as smoking and alcohol, rarer metabolic toxic agents should be screened for, in the index visit.…”
Section: Risk Factors and Clinical Coursementioning
confidence: 99%